Rattail fescue (Vulpia myuros) interference and seed production as affected by sowing time and crop density in winter wheat. Issue 1 (27th January 2021) - Akhter, Muhammad Javaid; Kudsk, Per; Mathiassen, Solvejg Kopp; Melander, Bo
Abstract: Field experiments were conducted in the growing seasons of 2017 to 2018 and 2018 to 2019 to evaluate the competitive effects of rattail fescue [ Vulpia myuros (L.) C.C. Gmel.] in winter wheat ( Triticum aestivum L.) and to assess whether delayed crop sowing and increased crop density influence the emergence, competitiveness, and fecundity of V. myuros . Cumulative emergence showed the potential of V. myuros to emerge rapidly and under a wide range of climatic conditions with no effect of crop density and variable effects of sowing time between the two experiments. Grain yield and yield components were negatively affected by increasing V. myuros density. The relationship between grain yield and V. myuros density was not influenced by sowing time or by crop density, but crop–weed competition was strongly influenced by growing conditions. Due to very different weather conditions, grain yield reductions were lower in the growing season of 2017 to 2018 than in 2018 to 2019, with maximum grain yield losses of 22% and 50% in the two growing seasons, respectively. The yield components, number of crop ears per square meter, and 1, 000-kernel weight were affected almost equally, reflecting that V. myuros 's competition with winter wheat occurred both early and late in the growing season. Seed production of V. myuros was suppressed by delaying sowing and increasing crop density. The impacts of delayed sowing and increasing crop density on seed production of V. myuros highlight the potential of these cultural weed control tactics in the long-term management programs of this species.